Synthesis and biological evaluation of novel 1,2,3-triazole hybrids of cabotegravir: identification of potent antitumor activity against lung cancer - Yajie Guo; Dan Sang; Bin Guo; Dan Wang; Dan Wang; Xinyue Xu; Xinyue Xu; Huili Wang; Cuilan Hou; Longfei Mao; Longfei Mao; Fang Li; et al. (Frontiers in Pharmacology, 2023)
In pursuit of discovering novel anticancer agents, we designed and synthesized a series of novel 1,2,3-triazole hybrids based on cabotegravir analogues. These compounds were subjected to initial biological evaluations to assess their anticancer activities against non-small-cell lung cancer (NSCLC). Our findings indicated that some of these compounds exhibited promising antitumor abilities against H460 cells, while demonstrated less efficacy against H1299 cells. Notably, compound 5i emerged as the most potent, displaying an IC50 value of 6.06 μM. Furthermore, our investigations into cell apoptosis and reactive oxygen species (ROS) production revealed that compound 5i significantly induced apoptosis and triggered ROS generation. Additionally, Western blot analysis revealed the pronounced elevation of LC3 expression in H460 cells and γ-H2AX expression in H1299 cells subsequent to treatment with compound 5i. These molecular responses potentially contribute to the observed cell death phenomenon. These findings highlight the potential of compound 5i as a promising candidate for further development as an anticancer agent especially lung cancer.